Extending collaborative learning beyong the boundaries of the physical classroom through virtual environments - Loureiro, Ana (2020)
In this paper we outline some of the potentialities and barriers of 3-D immersive virtual worlds when used in a learning context combined with other online tools. Classrooms can be extended from physical to virtual space in order to fulfill students’ needs and to facilitate a more collaborative learning style. Immersive learning allows us to learn in 1st person, allows us to have control over what we want to learn, how and when. The use of immersive 3-D virtual worlds allows students to participate in richer interactions at times that are more convenient to their work / study patterns, with no physical restrictions. Online web 2.0 tools, by being available at anytime and anywhere and user friendly, can enhance students’ collaboration and sharing, promote students’ socialization and improve classroom cohesion.